EWOLUCJA PRZEDSIĘBIORSTW W POLSCE W OKRESIE TRANSFORMACJI GOSPODARKI PO 1989 ROKU - Urbanowska-Sojkin, Elżbieta (Wydział Prawa i Administracji UAM, 2009)
The paper focuses on the changes in the activity of companies in Poland between 1989-2009. Those changes concern the goals o f business activity, methods of its realisation, both in respect of its fundamental function and supporting functions, and sources of the competitive advantage, market behaviours, particularly in relation to customers, competitors, vendors and other organisations from the business environment. Consequences o f globalisation, especially those seen in the fragmentation of economic activities and tools of its implementation (outsourcing and offshoring), deserve a special attention. Both development strategies have been used by Polish entrepreneurs. The business goals have undergone economic rationalisation, manifested as a necessity to solve problems such as the operating profitability of a given business or activity, the scope or extent of a given economic activity justifying its continuation, or cost-effectiveness of the traditional cooperative agreements. Today, transnational, or global, companies play a key role on the business market. Likewise, the role and impact o f the ideas and technologies of the information society are of fundamental importance. Furthermore, transformations in the organisation o f businesses are also important. Their structures are becoming better adapted to the current requirements of competitive markets and they substantially reduce fixed costs. For the purposes o f the study and to illustrate the changes taking place in the basic quantitative and qualitative features o f companies operating throughout Poland, the authors used statistical information published by Poland’s Main Statistical Office (GUS).
EVOLUTION OF POLISH COMPANIES DURING THE ECONOMY TRANSFORMATION AFTER 1989